Queen Size Variation in the Ponerine Ant Ponera coarctata (Hymenoptera: Formicidae) - J. Liebig; J. Heinze; B. Hölldobler (Psyche: A Journal of Entomology)
Queens of Ponera coarctata show a pronounced variation in size as measured by ommatidia number and Weber's alitrunk length. Isometric size variation and the normal distribution of size categories indicate that, despite these differences, only one queen morph exists. Queen size varies less within colonies than between colonies, and thus appears to be colony specific. Ovary length apparently varies with queen size. Similar size variations as in queens also occured in males, but not in workers.